The role of digital literacy in preventing the spread of political disinformation among first-time voters in Indonesia - Utami, Anak Agung Istri Dewi Adhi; Budiarta, I Wayan; Wirahyuni, Kadek; Sujana , I Putu Windu Mertha (Universitas Jambi, Indonesia, 2026)
The rapid development of information technology and social media has greatly enhanced the dissemination of political information in Indonesia, especially among first-time voters, a key demographic in elections. However, this increase in information flow has also heightened the risk of political disinformation, which can shape young voters’ perceptions, attitudes, and behaviors. Many first-time voters, due to their limited ability to verify information, are vulnerable to becoming both targets and spreaders of political hoaxes. This study examines the role of digital literacy in preventing the spread of political disinformation among first-time voters in Indonesia, focusing on access, evaluation, creation, ethical awareness, and active participation in online discourse. Through a Systematic Literature Review (SLR), the study analyzes relevant studies published between 2013 and 2024. The findings show that digital literacy enhances first-time voters' ability to verify information and avoid sharing unverified content. Strengthening digital literacy is crucial for enhancing democratic participation and mitigating the negative impacts of disinformation.